Ekspresi Enzim Rekombinan Reverse Transcriptase (RTRNase H) Simian Betaretrovirus Serotipe-2 Asal Macaca fascicularis Indonesia dalam Sistem Ekspresi Eschericia coli - Uus Saepuloh; Diah Iskandriati; Joko Pamungkas; Dondin Sajuthi (Jurnal Ilmu Pertanian Indonesia, 2013)
Reverse transcriptase (RT) enzyme is a key tool in molecular biology for the synthesis of complementary DNA (cDNA) from messenger RNA (mRNA). Combining RT activity with PCR amplification has been a gold standard as the first step in cloning the coding region of any gene of interest. Evidently, RTs have been critical in advancing molecular biology, genetics and medicine to their current stage. In this study, we were developing the RTDRNase H recombinant enzyme isolated from serotype-2 simian betaretrovirus-2 (SRV-2) infected Indonesian Macaca fascicularis using Escherichia coli expression system. The study was conducted using RT SRV-2 gene expression using E. coli expression system, proteins purification, and application to RT PCR technique. The SDS PAGE expression analysis showed a specific band size of 32.7 kDa assumed as RT protein enzyme. Application of RT SRV-2 enzyme generated to the RT PCR technique of β-globin CDV and SRV-2 env gene target showed that the RT SRV-2 enzyme was capable to reverse transcribed mRNA into cDNA as indicated by the presence of specific DNA band compared with commercial RT enzymes. This RT SRV-2 enzyme showed its activity similar to that of commercial one, although the activity was lower.